Clinicopathologic Features and Frozen Diagnostic Pitfalls of Bronchiolar Adenoma/Ciliated Muconodular Papillary Tumors (BA/CMPTs). (7th April 2023) - Ding, Bowen; Shang, Zhanxian; Xiang, Zhenzhen; Han, Yuchen
Abstract : To describe the histologic features of bronchiolar adenoma/ciliated muconodular papillary tumors (BA/CMPTs) and analyze the pitfalls in diagnosis from frozen sections. A total of 208 frozen and permanent sections of BA/CMPTs from Shanghai Chest Hospital from July 2018 to July 2021 were retrospectively analyzed. The median age of BA/CMPT patients was 65 years (15 to 79 y), and women accounted for 61.62% (122/198). The median size of BA/CMPTs was 0.6 cm (range 0.2 to 2 cm), of which 88.94% were small (≤1 cm, 185/208). In terms of location, the right lower lobe accounted for 44.23% (92/208), and the left lower lobe accounted for 33.65% (70/208). In 10 patients with 2 independent BA/CMPTs, 5 lesions were located in the left lower lobe and 4 in the right lower lobe. A total of 86.06% of the CT images of BA/CMPT showed solid/subsolid nodules (179/208). Among 208 tumors, 68.75% were distal type (143/208), and 31.25% were proximal type (65/208). The qualitative error rate of frozen sections was 21.33% (32/150), of which the distal type accounted for 75% (24/32); most of them were misdiagnosed as invasive adenocarcinoma during frozen diagnosis. The frozen diagnosis of BA/CMPTs might result in misdiagnosis as invasive adenocarcinoma. A careful search for characteristics of BA/CMPT, such as bilayer epithelial cells with basal cells and a lack of cellular atypia and invasive growth patterns, may be helpful for frozen diagnosis.